Polymer science and innovative applications : materials, techniques, and future developments - AlMaadeed, Mariam Ali; Ponnamma, Deepalekshmi; Carignano, Marcelo A. (Elsevier, 2020)
Polymer Science and Innovative Applications: Materials, Techniques, and Future Developments introduces the science of innovative polymers and composites, their analysis via experimental techniques and simulation, and their utilization in a variety of application areas. This approach helps to unlock the potential of new materials for product design and other uses. The book also examines the role that these applications play in the human world, from pollution and health impacts, to their potential to make a positive contribution in areas including environmental remediation, medicine and healthcare, and renewable energy. Advantages, disadvantages, possibilities, and challenges relating to the utilization of polymers in human society are included. Presents the latest advanced applications of polymers and their composites and identifies key areas for future development Introduces the simulation methods and experimental techniques involved in the modification of polymer properties, supported by clear and detailed images and diagrams Supports an interdisciplinary approach, enabling readers across different fields to harness the power of new materials for innovative applications.